Mapping the Network of Social Cognition Domains in Children With Autism Spectrum Disorder Through Graph Analysis - Pino, Maria Chiara; Vagnetti, Roberto; Masedu, Francesco; Attanasio, Margherita; Tiberti, Sergio; Valenti, Marco; Mazza, Monica (Frontiers in Psychiatry, 2020)
Children with autism spectrum disorder (ASD) are characterized by difficulties in social cognition (SC) domains. The aim of this study is to build an SC network to explore associations among interacting elements within this cognitive construct. We used a graph analysis to explain how individual SC domains relate to each other and how these relations may differ between ASD and typically developing (TD) groups. Seventy-six children with ASD and 81 TD children, matched for verbal mental age, were subjected to three SC measures. Our results showed that TD children exhibited an SC network characterized by a single domain (i.e., social cognition), while children with ASD demonstrated communicating node communities where social information processing measured by the Social Information Processing Interview (SIPI) represents a key point in understanding network differences between groups.